The Effect Of Moringa Leaf (Moringa Oleifera L.) Powder Substitution In Physicochemical And Organoleptic Characteristics Of Ice Cream - Rima Anjani; Akhmad Zakaria; Windy Widowaty (Universitas Pendidikan Indonesia, 2021)
Protein and calcium are two nutrients that are essential to the human body. These nutrients can be acquired through the consumption of animal and vegetable foods. Moringa leaves are a protein and calcium-rich vegetable dietary product. The goal of this study is to investigate the physicochemical and organoleptic properties of ice cream products by the addition of Moringa leaf powder. This study used an experimental method with a one-factor total randomized design. The addition of 0%, 3%, 6%, 9%, and 12% Moringa leaf powder treatment was carried out with 5 repetitions. The Kjeldahl method was used to analyse total protein content and Atomic Absorption Spectrophotometry was used to analyse the amount of Calcium in ice cream products. In this research, we tested the volume, mass, overrun, and melting time of ice cream, and so do the hedonic, and organoleptic characteristics. The results showed that calcium and protein levels of Moringa ice cream increased along with the addition of Moringa leaf powder. Ice cream with the addition of Moringa leaf powder by 12% had an average value of calcium and protein content higher compared to other ice cream samples. The addition of 9% Moringa leaf powder gave the best-overrun value of 47.86% which was determined based on the swelling power of the ice cream dough. Ice cream with 3% Moringa powder has the longest melting power of 12.82 minutes. organoleptic test results show that ice cream with 3% Moringa has the highest level of preference, with a total point of 527 for colour, 509 for aroma, 559 for taste, and 546 for texture. This study shows that Moringa leaves can be used as a substituent in ice cream.